Utilização de sistema de informação geográfica na avaliação do uso da terra em Botucatu (SP) - Rodrigues, J. B. T. [UNESP]; Zimback, Célia Regina Lopes [UNESP]; Piroli, E. L. [UNESP] (Sociedade Brasileira de Ciência do Solo, 2001)
The GIS-IDRISI was used to check land use adequacy from 1997 to 1998, in the initial part of the Rio Pardo basin, in Botucatu/Pardinho (SP), to obtain a suitable land use planning of the area. The classes and subclasses of land capability were determined according to the Land Capability Classification System. The lands of the studied area were classified as: class VIe, lands with erosion susceptibility (90.49%); class Va, flat lands, with no erosion risk, but limited by excess of water (3.48%); class IIIa, flat lands with excess of water (3.34%); class IIIe, lands with moderate slope and fast run-off, under severe erosion risk (1.32%); class IIe, productive lands, with small-to-moderate risk of erosion (0.87%); and class IVe, lands strongly limited by risk of erosion (0.50%). Based on the analysis of the current land use, it 89.28% of the area did not show conflict between the land capability and actual land use; 2.24% of the area was used with annual or perennial crops, but in lands with unsuitable for crops; and 8.48% of the area should be converted to forest and, or, environmental protection.

Foi utilizado o SIG-IDRISI, com o objetivo de verificar a adequação do uso da terra em 1997/98, na parte inicial da Bacia do Rio Pardo, Botucatu/Pardinho (SP), visando à obtenção de subsídios para o planejamento adequado do uso da área. As classes e subclasses de capacidade de uso foram determinadas de acordo com o Sistema de Classificação da Capacidade de Uso das Terras. As terras da área estudada foram discriminadas como: classe VIe, terras susceptíveis à erosão (90,49%); classe Va, terras planas, não-sujeitas à erosão, limitadas por excesso de água (3,48%); classe IVe, terras severamente limitadas por risco de erosão (0,50%); classe IIIa, terras planas com excesso de água (3,34%); classe IIIe, terras com declividade moderada e deflúvio rápido, riscos severos de erosão (1,32%); e classe IIe, terras produtivas, com risco ligeiro a moderado de erosão (0,87%). Pela análise conjunta da capacidade de uso e do uso atual das terras, verificou-se que 89,28% das áreas não apresentaram conflito de utilização; 2,24% estavam cultivadas com culturas anuais e perenes, adequação para tal uso, e 8,48% da área com pastagens deveria ser substituída por reflorestamento e, ou, preservação ambiental.
Utilization of a geographic information system on land use evaluation in Botucatu (SP)
Keywords: manejo do solo; geoprocessamento; classificação de terras; land use; GIS; soil management